Legal History of Extractive Industry Governance in Ethiopia - Silesh, Gizachew; Ahmed, Binnyam (Bahir Dar University Journal of Law, 2024)
Extractive Industries (EIs) are essential sources of economic and social development of a country. Current governance structures, extending from policies and laws pertaining to this sector are, in one way or another, the results of governance practices from the past. Even though the sector in Ethiopia has not grown to the expected level, the country had had a governance structure for this sector since the late 19th century. Over this stretch of time, there were governance systems regulating institutions engaged in mineral extraction activities. To fully understand the current governance structure, it is essential to analyse the sets of laws that were in place over that period. With this in view, the article evaluates the governance structure of extractive industries from the time of Emperor Menelik II to the time of the Derg. This is neither a denial of the existence of a governance framework in the pre-Menelik era nor a neglect of the developments in the governance of the sector after the Derg. Rather, this investigation is meant to draw insights from the extensive experience that could inform the current governance structure of extractive industries. By analyzing, through doctrinal legal analysis, the governance structures in place over those times, the article argues that since the inception of modern legal structures, the Ethiopian EI governance structure, though varied in depth, is informed by accumulated institutional experiences on the core issues related to EI governance. Accordingly, the paper further argues that an evaluation of the content of such historical legal documents is a first step to understanding the current institutional governance structure.